Comparative efficacy of black cumin and domperidone therapy on milk yield and fat percentage of indigenous cow (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The current study was designed to improve milk production and milk fat percentage by supplemented with black cumin and domperidone for thirteen weeks during lactation in indigenous cows. The experiment was performed in Kaligonjupazila of Lalmonirhat under the department of Physiology and Pharmacology, HSTU, Dinajpur, Bangladesh. At 7 days of lactation 16 deshi cows were randomly divided into 4 groups (n=4 lactating cows in each group). Group T1 was kept as control, Group T2 was treated with domperidone (Motigut®) orally at a dose of 100 mg /day per cow, Group T3 was treated with Black Cumin Seed Powder (BCSP) at a dose of 80 g orally per cow per day and Group T4 was treated with combination of domperidone with Black Cumin Seed Powder (BCSP) as above mentioned doses. All the animals were dewormed and vaccinated at initial stage. Over the course of the trial, observations were recorded for milk production and fat percentage in milk. Milk production were increased significantly (P